Efektivitas Penerapan Absensi Online (Face Detector) Untuk Meningkatkan Disiplin Pegawai Di Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Provinsi Bali - Debby Margareth Hutasoit; Putu Eka Purnamaningsih; Komang Adi Sastra Wijaya (Politeknik Kampar, 2023)
The aim of aplication online attendance (Face Detector) at the BKPSDM Bali Province is to increase the discipline of employees, both PNS and non-PNS employees. However, in its implementation, there are still some problems, such as application that still often crashes, employee absences that are often rejected, and employee abilities that are not evenly distributed. This study uses indicators of effectiveness based on Duncan in Kharisma (2017) which consist of three indicators of goal achievement, integration, and adaptation. The results of the study show the effectiveness of implementing online attendance (Face Detector) at the BKPSDM Bali Province.